The impact of management transparency in promoting organizational citizenship behavior – Field study on administrative staff at King Abdul-Aziz University Hospital in Jeddah Province – - Al-Amoudi, Tahani Mohammad; Zaki, Khadijah Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the impact of management transparency in promoting the behavior of organizational citizenship at King Abdul-Aziz University Hospital in Jeddah, as well as on the level of the hospital’s commitment to transparency, the obstacles to adopting transparency in the hospital, and the most important ways to help promote the adopting of the principle of transparency at King Abdul-Aziz University Hospital. The analytical descriptive approach was used, and to achieve the objectives of the study, the data were collected using a designed questionnaire, and the study community was made up of 534 administrative staff at King Abdul Aziz University Hospital in Jeddah, where the study was applied to a random sample of 224 singles, paper questionnaire distributed to them. The number of the recovered and valid questionnaires for analysis was 208. The results showed that the majority of the staff of the study sample agreed with the level of the hospital’s commitment to the application of transparency, where the response rates of the study sample on statements after the commitment ranged from 76% to 44%, and More than half of the study sample, at a rate of 53.4%, agreed that officials’ resistance to the application of transparency and that there is an impact of management transparency on the conduct of organizational citizenship at King Abdelaziz University Hospital in Jeddah. The study reached some recommendations, the most important of which are: raising the level of efficiency of the regulatory agencies by granting them sufficient powers and supporting them with human and material cadres; updating systems and simplifying work procedures; adopting recruitment and promotion policies on clear and stated standards; instilling the values of professional ethics and Self-censorship.